2006
DOI: 10.1016/j.immuni.2006.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Innate Immunity

Abstract: Adaptive immunity undergoes severe deterioration with age and represents the main problem in the elderly. However, evidence accumulated over the last decade supports the hypothesis that aging also has a profound impact on innate immunity, which in turn markedly impacts the health and longevity of older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
184
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 272 publications
(207 citation statements)
references
References 26 publications
13
184
0
5
Order By: Relevance
“…In spite of a chronic inflammatory state, aging has been thought to involve immunosenescence with deficient innate as well as adaptive immune response. [39][40][41][42] Mast cells are considered to be the first line of defense against allergens and pathogens and thus are important initiators of innate immune response. [43][44][45][46][47] Various inflammatory and chemotactic molecules produced and released from mast cells in response to foreign allergens or pathogens help recruitment of other antigen presenting cells at the site of inflammation and participate in shaping the host adaptive response.…”
Section: Aged Lymphatic Contractilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a chronic inflammatory state, aging has been thought to involve immunosenescence with deficient innate as well as adaptive immune response. [39][40][41][42] Mast cells are considered to be the first line of defense against allergens and pathogens and thus are important initiators of innate immune response. [43][44][45][46][47] Various inflammatory and chemotactic molecules produced and released from mast cells in response to foreign allergens or pathogens help recruitment of other antigen presenting cells at the site of inflammation and participate in shaping the host adaptive response.…”
Section: Aged Lymphatic Contractilitymentioning
confidence: 99%
“…Taken together, our findings indicate that in aging, mesenteric mast cells have reduced ability to be activated by acute inflammatory stimuli. While deficient immune cell function has been reported in aging, [39][40][41][42] there is no detailed information on the aging-associated alterations of mast cells and how they affect the function of mesenteric lymphatic vessels. The limited number of aged mast cells located in the mesentery to react to the presence of acute stimuli may be considered contributory to the aging-associated deteriorations in immune response.…”
Section: Aged Lymphatic Contractilitymentioning
confidence: 99%
“…Nevertheless, the pronounced age-related decrease in T-cell functions is evident, specially in the T-cell helper, which affects humoral immunity and causes an impaired B-cell function (2,7) . In the cells of innate immunity, the phagocytic cells show functions that decrease with ageing and others that are over activated (2,(11)(12)(13) , whereas the anti-tumoral activity of natural killer (NK) cells, in most of the work, shows an age-related decrease (2,11,14) . In addition, it has been demonstrated that the competence of the immune system is an excellent marker of health (2,4,8,15,16) and several age-related changes in immune functions, such as low T-cell proliferative responses, IL-2 secretion and NK cell cytotoxicity, have been linked to longevity (2,15,16) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…At least partly as a consequence, older populations experience increased morbidity and premature mortality, for example, from respiratory tract pathogens (Jartti et al 2011), an increase in gastrointestinal infections , and diminished antigenspecific responses to orally administered vaccines (Grubeck-Loebenstein et al 2009;Hagiwara et al 2003). Major age-related phenotypic and functional changes to the T-cell arm of adaptive immunity occur, while B-cell function (Frasca et al 2008) and the innate immune system (Solana et al 2006) may be less markedly affected.…”
Section: Introductionmentioning
confidence: 99%